Hyperbaric Oxygen Ameliorates The Expression of Tumor Growth Factor-β and Malondialdehyde in Pristane-induced Lupus Nephritis Mice Model - Soetjipto, Soetjipto; Murbani, Indri Dwi; Harnanik, Titut (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Lupus nephritis (LN) is associated with chronic renal failure and a high mortality rate. Tumor growth factor-β (TGF-β) plays a basic part in keeping up immune homeostasis, meanwhile extensive oxidation of the lipid membrane in LN causes the arrangement of malondialdehyde (MDA). Up to date, the mechanism of hyperbaric oxygen (HBO) therapy in LN has not been elucidated well. Hence this study was conducted to assess the impact of HBO therapy on TGF-β and MDA expression in the pristane-induced LN mice model.METHODS: Thirty-two mice aged 8-12 old weeks were isolated into 4 groups: normal saline-injected mice (group 1); pristane-injected mice (group 2); as well as pristane-injected followed by HBO-exposured with 2.4 (group 3) and 1.5 (group 4) atmosphere absolute (ATA) pressure. Pristane were injected intraperitoneal to initiate LN. Two months after pristane injection, the mice were placed within 24 hours in the special cage for metabolic examination to determined that pristane-induced LN mice model was successfully formed and marked by the occurring proteinuria. Oxidative stress was assessed by examining MDA, while systemic inflammation was assessed by examining by TGF-β. MDA and TGF-β serum were measured by enzyme-linked immunosorbent assay (ELISA).RESULTS: A significantly lower (p<0.050) MDA expression was found in group 3 in comparison with group 2. The results also showed that TGF-β level was significantly increased (p<0.050) in group 3 compared to group 2.CONCLUSION: HBO therapy ameliorates inflammation in LN by diminishing MDA and expanding TGF-β levels through activating antioxidants.KEYWORDS: lupus nephritis, hyperbaric oxygen, malondialdehyde, tumor growth factor-β